2012
DOI: 10.1124/jpet.112.195701
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Spine Injury Induced by the 8-Hydroxy Metabolite of Efavirenz

Abstract: Despite combination antiretroviral therapies (cARTs), a significant proportion of HIV-infected patients develop HIV-associated neurocognitive disorders (HAND). Ongoing viral replication in the central nervous system (CNS) caused by poor brain penetration of cART may contribute to HAND. However, it has also been proposed that the toxic effects of long-term cART may contribute to HAND. A better understanding of the neurotoxic potential of cART is critically needed in light of the use of CNS-penetrating cARTs to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
94
2
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(107 citation statements)
references
References 52 publications
2
94
2
1
Order By: Relevance
“…Interestingly, we have shown how there is significant accumulation in the seminal plasma of the hydroxylated metabolites of EFV, which may impact local pharmacology and/or toxicology. Future work may involve examination of the potential for local toxicity in compartments such as the male genital tract, where we have found oxidative metabolites to accumulate, including 8-OH EFV, which has been demonstrated to induce compartment-specific mechanisms of toxicity (Bumpus, 2011;Tovar-Y-Romo et al, 2012). Taken together, this study is the first to demonstrate the anatomic distribution of metabolites of an ARV into relevant biologic compartments and to examine their anti-HIV activity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Interestingly, we have shown how there is significant accumulation in the seminal plasma of the hydroxylated metabolites of EFV, which may impact local pharmacology and/or toxicology. Future work may involve examination of the potential for local toxicity in compartments such as the male genital tract, where we have found oxidative metabolites to accumulate, including 8-OH EFV, which has been demonstrated to induce compartment-specific mechanisms of toxicity (Bumpus, 2011;Tovar-Y-Romo et al, 2012). Taken together, this study is the first to demonstrate the anatomic distribution of metabolites of an ARV into relevant biologic compartments and to examine their anti-HIV activity.…”
Section: Discussionmentioning
confidence: 89%
“…Recently, we demonstrated for the first time that 8-OH EFV has the ability to induce cytotoxicity via stimulation of mitochondrial dysfunction and activation of stress-activated signaling pathways (Bumpus, 2011). Subsequently, toxicity of 8-OH EFV to dendritic cells of the CNS has also been reported (Tovar-y-Romo et al, 2012). Although the mechanisms underlying the adverse effects of EFV on semen quality have yet to be fully elucidated, it has been reported that treatment with EFV results in decreased motile spermatozoa and vitality, suggested to be the result of mitochondrial toxicity or direct toxicity to the cells producing spermatozoa (van Leeuwen et al, 2008;Lambert-Niclot et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these studies, the most noted adverse events associated with the efavirenz-containing regimen were psychiatric symptoms and rash; however, the molecular mechanism(s) that underlie the differences in the safety profiles of RPVcontaining versus efavirenz-containing regimens is unknown (6,7). While we recently demonstrated that the primary metabolite of efavirenz, 8-hydroxyefavirenz, may play a causal role in efavirenz-mediated toxicities, including hepatic and neuronal toxicity, this type of analysis is not yet possible for RPV, as the metabolites of this drug have yet to be defined (8,9).…”
Section: R Ilpivirine (Rpv; Edurant) 4-[[4-[[4-[(1e)-2-cyanoethenyl]mentioning
confidence: 99%
“…Furthermore, there are secondary metabolites associated with products of primary metabolism [4,5]. A relatively fewer number of studies have attempted to link efavirenz induced CNS toxicity with 8-hydroxefavirenz [6,7]. A possible metabolites movement carrier in a patient who had been on efavirenz is suggested.…”
Section: Introductionmentioning
confidence: 99%